Platelet-Rich Fibrin in Fat Grafts for Facial Lipofilling: A Randomized, Controlled Split-Face Clinical Trial - Zhang, Zhao-Xiang; Qiu, Li-Hong; Shi, Nian; Xiong, Shao-Heng; Ma, Xian-Jie; Yi, Cheng-Gang (Frontiers in Surgery, 2022)
Objective: Previous studies have reported that platelet-rich fibrin (PRF) may enhance the efficacy of fat grafts in facial lipofilling. However, these studies either lacked objective data or were not randomized, controlled trials. Thus, we aimed to objectively evaluate the efficacy of PRF in facial lipofilling. Methods: A controlled, split-face, randomized trial (January 2018 to May 2019) based on 18 patients who underwent fat grafts for bilateral temple lipofilling was performed. Each patient received a combination of an autologous fat graft and PRF on one side and a fat graft combined with an equal volume of saline on the other side. The effects of PRF were evaluated by comparing the remaining bilateral fat graft volumes through a digital three-dimensional reconstruction technique. Improvements in the appearance and recovery time of each temple were assessed by both a surgeon and patients who were blinded to the treatment assignment. Complications were also recorded. Results: Bilateral temple lipofilling showed no evidence of fat embolism, vascular/nerve injury, infection, massive edema, or prolonged bruising. Three-dimensional reconstruction data and the assessments from both the surgeon and patients revealed no significant differences in fat graft retention volume between the PRF-positive and PRF-negative lipofilling groups. However, recovery time in the PRF-positive lipofilling sites was significantly shortened compared with that of the PRF-negative lipofilling sites. Conclusion: Facial filling with autologous fat grafts is effective and safe. Our results show that PRF does not markedly improve fat graft volume retention in the temple but significantly reduces postoperative recovery time.